The Effects of Full-Time Versus Part-Time Employment Status on Attitudes Toward Specific Organizational Characteristics and Overall Job Satisfaction - Eberhardt, Bruce J.; Shani, Abraham B. (Academy of Management Journal, 1984)
The article focuses on a comparative study which examined the attitudes toward specific organizational characteristics and feelings of overall job satisfaction between part-time employees and full-time employees. Questionnaires were distributed by the hospital administration to the 397 employees of a medical rehabilitation hospital. The questionnaire consisted of 50 statements describing various aspects of an organization. Experts say the study has several limitations. Several of the dependent variable scales had only marginal reliabilities. Also the generalization of the study results is restricted by the nature of the sample.